Surgical Management of Acute Distal Biceps Tendon Ruptures. (3rd May 2017) - Savin, David D.; Watson, Jonathan; Youderian, Ari R.; Lee, Simon; Hammarstedt, Jon E.; Hutchinson, Mark R.; Goldberg, Benjamin A.
Abstract : Acute distal biceps tendon ruptures are uncommon injuries that often affect young active males and typically result from an eccentric load on the dominant upper extremity. Surgical treatment may be indicated to prevent substantial weakness in supination and flexion that can occur with nonoperative treatment. Nonoperative management should be reserved for elderly or less active patients with multiple comorbidities, especially when the injury involves the nondominant arm. Operative management can be performed using a single-incision or dual-incision technique, with multiple surgical options for tendon-to-bone fixation. Single-incision repair techniques are more likely to be complicated by a transient neurapraxia, most often involving the lateral antebrachial cutaneous nerve, while dual-incision repair techniques are more likely to be complicated by heterotopic ossification and stiffness.